Development Of Interactive E-Modules Based On Animated Videos To Improve Critical Thinking Skills In History Learning Media Courses - Sidiq, Ric; Najuah, N; Syarifah, Syarifah; Saragih, Anggi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research aims to produce interactive E-Module products based on animated videos to improve critical thinking skills in history learning media courses. The target of this research is products developed /valid for use according to experts and users. The method used is the research and development method or Research &; Development (R&D). To produce the product, testing its feasibility and effectiveness is carried out in accordance with the development goals. The research was carried out in the Department of History Education with the observed modifiers, namely history education students class of 2020 as the target targets and products developed. Data collection techniques are carried out through observation, and questionnaires. With data analysis techniques with qualitative descriptive and quantitative descriptive. From the results of the research conducted, data were obtained: 1). The results of material expert validation received a value of 75 with a percentage of 93.75% in the